Gender Perceptions in Lebanon: A Case Study of how Gender is Perceived in Lebanon and the Factors that Influence the Perceptions - Bitar, Khuloud (2024)
Thesis (M.A.) -- Interdisciplinary Gender Studies, May 2024.